IMPROVING CHILDREN'S ENGLISH ABILITY IN INTRODUCTION OF ADL VOCABULARY THROUGH PICTURE MEDIA AT KINDERGARTEN OF PKK PARANG 1 BULAKDAWUNG, KEDIRI REGENCY - Yoyok Febrijanto; Sandy Kurniajati; Erva Elli Kristanti; Abram Sinar Saktiya; Otniel Febritian Christada; Devina Marsaulina Nababan; Imelda Amelia; Anette Von Bone; Hannah Anich; Micah Erickson; Laurent Workman (Suluh Adiluhung Publisher (SAPub), 2025)
This community service is based on the results of observations and research experiences during the implementation of learning to recognize vocabulary in the language development of children who are less able to understand the teacher's explanation, not all children can imitate vocabulary and mention it correctly. The purpose of this community service is to improve English language skills in recognizing ADL vocabulary with picture media using the Class Action approach in children at Kindergarten of PKK Parang 1, Bulakdawung, Kediri Regency, totaling 12 children. The results show that children's English skills in independence, and accuracy in children, most of the children have reached the Developing According to Expectations (Berkembang Sesuai Harapan) stage with the following details: for the independence aspect 79.17%, and for the accuracy aspect 72.92%. While the average percentage of all three reached 76.04%. Thus, it can be concluded that the hypothesis of action to improve children's language skills in the activity of recognizing ADL Vocabulary with picture media in children aged 5-6 years at Kindergarten of PKK Parang I, Bulakdawung, Kediri Regency can be accepted.